THE SCIENTIFIC USE OF THE UKRVO JOINT DIGITAL ARCHIVE: GRBs FIELDS, PLUTO, AND SATELLITES OF OUTER PLANETS - Vavilova, I.; Golovnya, V.; Andruk, V.; Pakuliak, L.; Yizhakevych, O.; Shatokhina, S.; Protsyuk, Yu.; Kazantseva, L.; Lukianchuk, V. (Одеські астрономічні публікації, 2014)
In the framework of UkrVO national project the new methods of plate digital image processing are developed. The photographic material of the UkrVO Joint Digital Archive (JDA – http://gua.db.ukr-vo.org/vo-mao/DB/archivespecial.php) is used for the solution of classic astrometric problem – positional and photometric determinations of objects registered on the plates. The results of tested methods show that the positional rms errors are better than ±150 mas for both coordinates and photometric ones are better than ±0.20m with the Tycho-2 catalogue as reference.